The date of publication of ‘Decapoden-Studien … auf A. B. Meyer’s Sammlungen im ostindischen Archipel’ by Johann Thallwitz and its bearing on decapod nomenclature (Crustacea: Decapoda) - Low, Martyn E. Y. (Zootaxa, 2017)
Johann Thallwitz was an assistant curator at the Königlichen zoologischen Museum zu Dresden, Germany (Holthuis 1959: 15). Thallwitz’s publication entitled ‘Decapoden-Studien, inbesondere basirt auf A. B. Meyer’s Sammlungen im ostindischen Archipel, nebst einer Aufzählung der Decapoden und Stomatopoden des Dresdener Museums’ (hereafter the ‘Decapoden-Studien’) which appeared in the 1890–1891 volume of the Abhandlungen und Berichte aus dem Königlichen Zoologischen und Anthropologisch-Ethnographischen Museums zu Dresden (hereafter the Abhandlungen) is important for decapod nomenclature as eighteen species and three genus-group names were declared to be new therein (see below).